The miniJPAS survey: stellar atmospheric parameters from 56 optical filters. Issue 2 (4th November 2022) - Yuan, H-B; Yang, L; Cruz, P; Jiménez-Esteban, F; Daflon, S; Placco, V M; Akras, S; Alfaro, E J; Galarza, C Andrés; Gonçalves, D R; Duan, F-Q; Liu, J-F; et al.
ABSTRACT: With a unique set of 54 overlapping narrow-band and two broader filters covering the entire optical range, the incoming Javalambre-Physics of the Accelerating Universe Astrophysical Survey (J-PAS) will provide a great opportunity for stellar physics and near-field cosmology. In this work, we use the miniJPAS data in 56 J-PAS filters and 4 complementary SDSS-like filters to explore and prove the potential of the J-PAS filter system in characterizing stars and deriving their atmospheric parameters. We obtain estimates for the effective temperature with a good precision (<150 K) from spectral energy distribution fitting. We have constructed the metallicity-dependent stellar loci in 59 colours for the miniJPAS FGK dwarf stars, after correcting certain systematic errors in flat-fielding. The very blue colours, including uJAVA − r, J 0378 − r, J 0390 − r, uJPAS − r, show the strongest metallicity dependence, around 0.25 mag dex −1 . The sensitivities decrease to about 0.1 mag dex −1 for the J0400 − r, J0410 − r, and J 0420 − r colours. The locus fitting residuals show peaks at the J 0390, J 0430, J 0510, and J 0520 filters, suggesting that individual elemental abundances such as [Ca/Fe], [C/Fe], and [Mg/Fe] can also be determined from the J-PAS photometry. Via stellar loci, we have achieved a typical metallicity precision of 0.1 dex. The miniJPAS filters also demonstrate strong potential in discriminating dwarfs and giants, particularly the J 0520 and J 0510 filters. Our results demonstrate the power of the J-PAS filter system in stellar parameter determinations and the huge potential of the coming J-PAS survey in stellar and Galactic studies.